Diminished Myoinositol in Ventromedial Prefrontal Cortex Modulates the Endophenotype of Impulsivity. (2nd January 2020) - Jupp, Bianca; Sawiak, Steve J; van der Veen, Bastiaan; Lemstra, Suzanne; Toschi, Chiara; Barlow, Rebecca L; Pekcec, Anton; Bretschneider, Tom; Nicholson, Janet R; Robbins, Trevor W; Dalley, Jeffrey W
Abstract: Maladaptive impulsivity manifests in a variety of disorders, including attention-deficit hyperactivity disorder (ADHD), depression, and substance use disorder. However, the etiological mechanisms of impulsivity remain poorly understood. In the present study, we used in-vivo proton magnetic resonance spectroscopy ( 1 H-MRS) to investigate neurometabolite content in the prefrontal cortex (PFC) and striatum of rats exhibiting low- versus high-impulsive (LI, HI) behavior on a visual attentional task. We validated our 1 H-MRS findings using regionally resolved ex-vivo mass spectroscopy, transcriptomics, and site-directed RNA interference in the ventromedial PFC. We report a significant reduction in myoinositol levels in the PFC but not the striatum of HI rats compared with LI rats. Reduced myoinositol content was localized to the infralimbic (IL) cortex, where significant reductions in transcript levels of key proteins involved in the synthesis and recycling of myoinositol (IMPase1) were also present. Knockdown of IMPase1in the IL cortex increased impulsivity in nonimpulsive rats when the demand on inhibitory response control was increased. We conclude that diminished myoinositol levels in ventromedial PFC causally mediate a specific form of impulsivity linked to vulnerability for stimulant addiction in rodents. Myoinositol and related signaling substrates may thus offer novel opportunities for treating neuropsychiatric disorders comorbid with impulsive symptomology.